Istilah yang Digunakan Gubernur Sumatera Barat dalam Mengatasi Penyebaran Covid-19 - Ria Febrina; Sri Wahyuni (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This research aims to (1) describe, (2) explain the impact, and (3) recommend terms used by the Governor of West Sumatra in dealing with the spread of Covid-19. This research was conducted by listening and noting terms in words, phrases, and sentences used by the Governor of West Sumatra, then analysing the term and presenting research results in explanatory sentences. The results showed that (1) the terms used by the Governor of West Sumatra consisted of three forms, namely words, phrases, and abbreviations; (2) the use of the term has an impact on the social, psychological, economic, and cultural conditions of the Minangkabau community; and (3) determine the number of appropriate terms in dealing with Covid-19.